Nasal Reconstruction Involving Multiple Subunit Defects - Cox, Artemus; Fort, Matthew (Facial Plastic Surgery, 2017)
The challenges of nasal reconstruction are readily apparent to any surgeon who has undertaken this task. Defects involving multiple subunits of the nose usually require adjacent tissue transferred to the wound typically in the form of a forehead flap or other local flaps. Herein, we describe current thought on the subunit principle and the application of local flaps and grafts in reconstructing larger superficial defects of the nose. Primary attention is paid to analysis and patient counseling.
Keywords: nasal reconstruction; subunit principle; forehead flap